Introgressão e deslocamento de caracteres numa zona de contato entre Picumnus varzeae e Picumnus cirratus macconnelli no Rio Amazonas - Santana, Hevana de Lima (Instituto Nacional de Pesquisas da Amazônia - INPA, 2018)
The genus Picumnus represents a highly diverse group with relationships among species poorly resolved and taxonomic coverage incomplete. In this work, we use species of the genus Picumnus to examine two distinct aspects. In the first chapter, we examined vocal variation within Picumnus, considering all known species and subspecies available in sound archives, analyzing traits of songs in each species and subspecies. With our analyses, we aim not only to recognize species groups within the genus Picumnus, but also to elucidate the differences at the species level that could be hidden within the currently recognized species. For the second chapter, we examined two species of the genus Picumnus, inhabitants of the Amazonian lowland forests, Picumnus varzeae and Picumnus cirratus macconnelli, we analyzed whether patterns of variation in morphometric, bioacoustic and plumage characters in P. varzeae would be consistent with the hypothesis hybridization, or character displacement between these two species. In the first chapter, we found two major, distinct vocal groups within the Picumnus, the first one consisting of species with trilled sounds, fast, with a large number of notes per sound, and the second one, formed by species with tss-tss sounds, slow songs, with few notes per song, the species that formed these two groups, when compared, showed similarities to existing phylogenies of woodpeckers based on molecular data. In the second chapter, we show that P. varzeae and P. c. macconnelli are two species in fact come into contact in a narrow contact zone, about 100 km in the Óbidos region, in the Brazilian state of Pará. The variation in plumage pattern found in P. varzeae at points distant from the contact zone, would then be the result of events of phenotypic introgression between the two species and the effect of character displacement along the distribution of the P. varzeae population. This is the first study to describe the vocal variation of species of the genus Picumnus. It was also the first study to focus on the events occurring in contact zones between species of birds endemic to the Amazonian floodplain and the first case of displacement of character reported in a taxon of the Brazilian Amazon.
Keywords: Aves; Picumnus; Várzea; Vocalização; Zona de contato